Match-Related Statistics Differentiating Winning and Losing Teams at the 2019 Africa Cup of Nations Soccer Championship - Kubayi, Alliance; Larkin, Paul (Frontiers in Sports and Active Living, 2022)
This study investigated game-related statistics differentiating winning and losings teams of matches during the 2019 African Cup of Nations (AFCON) soccer tournament. The sample consisted of 38 games, with data obtained from the InStat Scout platform. Data were analysed using mean (M), standard deviation (SD), effect size (ES), structure coefficients (SCs) and the Wilcoxon signed-rank test. The results showed that winning teams performed significantly better than losing teams in terms of shots (M = 12.13, SD = 4.67, Z = −2.26, ES = 0.62), shots on target (M = 5.05, SD = 2.54, Z = −4.22, ES = 1.13), and shots from counter-attacks (M = 2.24, SD = 1.42, Z = −2.48, ES = 0.57). Shots on target (SC = 1.22), shots (SC = −0.73), fouls (SC = 0.60), total passes (SC = 0.44), and yellow cards (SC = −0.32) presented the highest discriminatory power. The findings highlight the key match performance variables which influence game results and may assist coaches in developing and implementing team strategies to improve the likelihood of winning the AFCON championship.